2001
DOI: 10.1037/0097-7403.27.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern learning in rats: Control by an iterative pattern.

Abstract: Rats searched in a matrix of vertical poles for food hidden on top of the poles. The only information available about the location of the food was the consistent spatial pattern of the baited poles, which was a checkerboard. This spatial pattern of hidden-food locations came to control the choices of poles made by the rats. The experiments ruled out the possibility that this control can be explained by the acquisition of simple response tendencies to move from pole to pole. Instead, this behavioral control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…In this case, the measure was the one developed by Brown et al (2001) for the checkerboard pattern. This measure is the relative tendency to choose a pole as a function of its spatial relationship to the most recently chosen pole and whether the most recently chosen pole was baited or not.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, the measure was the one developed by Brown et al (2001) for the checkerboard pattern. This measure is the relative tendency to choose a pole as a function of its spatial relationship to the most recently chosen pole and whether the most recently chosen pole was baited or not.…”
Section: Resultsmentioning
confidence: 99%
“…Both exemplars form a checkerboard pattern, much like the white or black spaces on a chessboard. Brown et al (2001) found that rats learn to choose poles in conformity with this pattern and that their performance cannot be explained in terms of learning relatively simple response tendencies. Thus, they argued, rats learn at least some of the spatial relations among the poles forming a checkerboard pattern.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations